2003
DOI: 10.1128/jcm.41.4.1486-1493.2003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PCR as a Diagnostic Mass-Screening Tool To Detect Leishmania ( Viannia ) spp. in Domestic Dogs ( Canis familiaris )

Abstract: Several studies have suggested that the PCR could be used in epidemiological mass-screening surveys to detect Leishmania (Viannia) spp. infection in human and animal hosts. Dogs from an area of Leishmania braziliensis and Leishmania peruviana endemicity were screened for American cutaneous leishmaniasis (ACL) infection by established PCR-based and enzyme-linked immunosorbent antibody test (ELISA) protocols. PCR detected Leishmania (Viannia) infection in a total of 90 of 1,066 (8.4%) dogs: 32 of 368 (8.7%), 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
(74 reference statements)
4
22
1
1
Order By: Relevance
“…The technique has been consistently validated as the fastest and most sensitive and specific one as compared to other diagnosis protocols -apart from its suitability when used in leishmaniasis surveillance programs 2,[8][9][10][11] . Concerning molecular diagnosis, kinetoplast DNA minicircles (KDNA) are good targets in the Leishmania genome, as these present up to 10,000 copies per cell, which increases sensitivity of detection procedures 2,12 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The technique has been consistently validated as the fastest and most sensitive and specific one as compared to other diagnosis protocols -apart from its suitability when used in leishmaniasis surveillance programs 2,[8][9][10][11] . Concerning molecular diagnosis, kinetoplast DNA minicircles (KDNA) are good targets in the Leishmania genome, as these present up to 10,000 copies per cell, which increases sensitivity of detection procedures 2,12 .…”
Section: Methodsmentioning
confidence: 99%
“…Despite the difficulties associated to the interpretation of seroprevalence data, the Health Ministry of Brazil recommends that serological diagnosis be performed based on sampling and population surveys 1 . Also, non-specific cross-reactions and delay between infection and seroconversion occur often 8 .…”
Section: Article/artigomentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, the polymerase chain reaction (PCR) has been successfully introduced and proven to be a sensitive and powerful tool to detect Leishmania in clinical samples as well as for parasite characterization [21][22][23]. Very recently, PCR has also been used to analyse the immune response profile either in humans or in infected dogs [24].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in South America have shown that dogs can be experimentally infected with L. ( Viannia ) species and that a high proportion of the canine population is naturally infected. [5][6][7][8][9] However, dog infections have not been characterized in areas where Leishmania ( Viannia ) guyanensis is transmitted.…”
Section: Introductionmentioning
confidence: 99%